Optimasi Omzet Penjualan dan Harga Jual Kacang Kapri dalam Memperoleh Laba (Studi Kasus pada UD Monang) - WIDYANTARA, I WAYAN; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.3, Juli 2016, 2016)
Optimizing Sales Turnover and Price of Kapri RoastedPeanuts in Obtaining Profit (A Case Study at UD Monang) The development of small businesses, particularly agro-industries should be gettingmore attention, because it is very vulnerable to any risks as a result of uncertainty inthe field of farming and the lower quality of Human Resources on small businesses.It is necessary for improvement in the management in order to be able to earn aprofit in the long run. The management of agro-industry, especially smallbusinesses, is an important topic that should continuously be improved and studiedin order to reach more effective management. The purpose of this study is: to findout the sales turnover to be done in order to obtain maximum profits, to determinehow the sales volume each month that must be offered in order not to lose, whatprice per kg should be offered to customers, and whether UD Monang has thebargaining position in selling its roasted kapri peanuts. The results of the studyindicated that the peanuts’ optimal sales volume, so that UD Monang can gainmaximum profit if UD Monang is able to sell peanuts 2,875.67 kg/month. Thecritical point of losses occurred on the sales volume of 1,013.58 kg/month. Theselling price of peanut offer should range between IDR 27,000.00/kg. to IDR37,558.50/kg. UD Monang’s bargaining position was 34% of the agreed price bythe customers / consumers.
Keywords: agro-industry, kapri roasted peanuts, sales, selling prices